Design and build a machine for transporting bottle trash in ditches with a gamepad control - Tianur; Aji Saputra; Edilla (JTTM : Jurnal Terapan Teknik Mesin, 2023)
In Indonesia, flooding is frequently brought on by the issue of garbage in ditches. Plastic bottle garbage is one of the waste forms that is frequently found. Because of this, a machine to collect gutter bottle waste and raise the bottle waste from ditches must be made. The operator can use a gamepad to control this DC motor-driven equipment. A chain transmits the rotation of the DC motor to the engine driving wheel. A chain that has been transformed into a conveyor is used as part of the system for lifting trash from the gutter to the storage tanks. The wheel base can be manually shifted to change the wheel width from 80 cm to 120 cm. The machine has a success rate of 76.6% while lifting waste, and it can move forward or backward across the ditch at a speed of 0.041-0.042 m/s while transferring up to 3 spinning waste bottles. This device can significantly help with efforts to improve the gutter environment and lower the chance of flooding brought on by rubbish clogging.